Pemanfaatan Wolffia arrhiza Pada Ikan Mas Berdasarkan Evaluasi Pertambahan Bobot Badan, Konversi Ransum, dan Kualitas Daging - Toga Mahaji; Mhd. Aidil Huda J; Shofian Nanda Adiprayoga; Angelia Utari Harahap (Samakia : Jurnal Ilmu Perikanan, 2024)
Wolffia (Wolffia arrhiza) is thought to be a ration substitute for goldfish because it has a nutritional content of 34-45% protein along with essential amino acids, low crude fiber content ranging from 10-11%, starch content of 10-20% and fat of 1-5% . The aim of this research was to look at the effect of using Wolffia arrhiza on goldfish on evaluating body weight gain, feed conversion and meat quality. This research method uses a Completely Randomized Design (CRD) experimental design with 4 treatments and 3 replications consisting of 4 tilapia fish in each replication. The parameters tested were body weight gain, ration conversion, and carp meat quality. This research shows that the use of fresh wolffia as goldfish rations has a good influence on body weight growth of 7.5 grams with a ration conversion value of 2.3 and meat quality based on meat protein content of 15.35%. The fresh wolffia formulation showed the best growth results in the D treatment with 20% fresh wolffia with 80% artificial pellets on goldfish. It is thought that Wolffia (Wolffia arrhiza) can be used as a ration substitute for goldfish because it has a nutritional content of 34-45% protein and essential amino acids, low crude fiber content ranging from 10-11%, starch content of 10-20% and fat of 1-5% . The aim of this research was to look at the effect of using Wolffia arrhiza on goldfish on evaluating body weight gain, feed conversion and meat quality. This research method uses a Completely Randomized Design (CRD) experimental design with 4 treatments and 3 replications consisting of 6 tilapia fish in each replication. The parameters tested were body weight gain, ration conversion, and carp meat quality. This research shows that the use of fresh wolffia as goldfish rations has no significant effect (P>0.5) on body weight growth of 7.50 grams with a ration conversion value of 2.31 and meat quality based on meat protein content of 14.59%. . The fresh wolffia formulation showed the best growth results in treatment D with treatment of 20% fresh wolffia with 80% artificial pellets on goldfish.